DEMOGRAPHIC AND CLINICAL CHARACTERISTICS OF PATIENTS REFERRED TO PSYCHIATRIC UNIT IN A TERTIARY CARE HOSPITAL - Yousafzai, Abdul Wahab; Jehangiri, Attique ur Rehman; Kazim, Mehrunissa; Shah, Mubashir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Very few studies from Pakistan have examined the profile of patients seen by psychiatrists in general hospital. The aim of this research is to describe the clinical and demographic characteristics of patients referred to the psychiatric unit of a general hospital over a one year period. Methods: This cross-sectional study was conducted at the Ayub Teaching Hospital, Abbottabad, from January 1st to December 31st 2012. All patients being referred to psychiatry were included in the study over one year period. The information was recorded on a structured questionnaire and analysed the data using SPSS-19.0. Results: Out of the 105 patients referred to the psychiatric unit, 74 (72.3%) were females. A total of 69 (68.5%) patients were married. More than half were uneducated and only number 4 (3%) patients had university qualification. Housewives made up 64.4% of the patient population followed by students (11%). Majority 55 (53%) had less than Rs. 5000/ monthly income. About 30% patients were shifted to psychiatry ward while, nearly one tenth were discharged. In 35% cases the psychiatrist was asked to help in the management, while in 50% cases only opinion was sought. Aggressive and threatening behaviour was source of concern in majority of patients for the primary team while 34% exhibited suicidal behaviour. Depression was most frequent diagnosis in 45 43% patients, followed by conversion disorder 19 (17%) and delirium 16 (14%). Conclusion: The rate of psychiatric referrals is dismal with only one third of the patients being transferred to the psychiatric ward. The major psychiatric diagnosis was depression. Patients with aggressive and threatening behaviour were more frequently referred. Keywords: General hospital, psychiatry, psychiatric referrals, consultation liaison psychiatry